2002
DOI: 10.1034/j.1399-0004.2002.610104.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the angiotensin‐converting enzyme D/I polymorphism and left ventricular remodeling in the ‘Healing and Early Afterload Reducing Therapy’ Study

Abstract: The D/I (deletion, D, insertion, I) polymorphism of the angiotensin-converting enzyme (ACE) gene has been extensively studied for its association with a number of cardiovascular and other disease states. However, its potential association with differential clinical efficacy of ACE inhibitors (ACE-I) administered to patients who had suffered a myocardial infarction (MI), i.e. the prevention of left ventricular (LV) remodeling, has so far not been specifically studied. The aim of the study was to investigate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Zee and colleagues, in a substudy of the Healing and Early Afterload Reducing Therapy Study, evaluated the effects of ramipril (target dose of 10 mg daily) on left ventricular remodeling post-myocardial infarction in 265 patients with ACE genotyping performed. [82] In contrast to the Pinto study, this investigation found no evidence for an association between the ACE DD genotype and risk for remodeling in the setting of ACE inhibitor use. This study followed left ventricular echocardiographic parameters for only 90 days following the acute event and thereby may be limited in extrapolating longterm differences in remodeling among genotypes.…”
Section: Left Ventricular Remodeling Post-myocardial Infarctionmentioning
confidence: 91%
“…Zee and colleagues, in a substudy of the Healing and Early Afterload Reducing Therapy Study, evaluated the effects of ramipril (target dose of 10 mg daily) on left ventricular remodeling post-myocardial infarction in 265 patients with ACE genotyping performed. [82] In contrast to the Pinto study, this investigation found no evidence for an association between the ACE DD genotype and risk for remodeling in the setting of ACE inhibitor use. This study followed left ventricular echocardiographic parameters for only 90 days following the acute event and thereby may be limited in extrapolating longterm differences in remodeling among genotypes.…”
Section: Left Ventricular Remodeling Post-myocardial Infarctionmentioning
confidence: 91%
“…However, several inconsistencies are evident in the findings of some hypertension, left ventricular hypertrophy and cardiomyopathy studies, and consequently the extent of the modification effect of this polymorphism remains unclear [46][47][48][49][50]. A meta-analysis assessed the possibility of an association between the ACE I/D polymorphism and the response to ACE inhibitors among 4 previously published pharmacogenetic reports that included a total of 925 patients.…”
Section: Ace Polymorphisms and Ace Inhibitor Drug Responsementioning
confidence: 98%
“…However, the data concerning the association of ACE polymorphism and LV remodeling after MI remain controversial. While some studies showed an association of the D allele with greater mortality and increased LV dilatation and hypertrophy [43,44,45,46], others found no or only weak association between them [40,47,48,49].…”
Section: Polymorphism Of Angiotensinconverting Enzymementioning
confidence: 99%